THE EFFECT OF BRAND IMAGE AND SERVICE QUALITY ON LOYALTY THROUGH PATIENT SATISFACTION AS AN INTERVENING VARIABLE AT CLINIC A IN KUDUS CITY (Study at Clinic A in Kudus City, Central Java) - Ayu Rindwita Indah Peanasari; Vip Paramarta; Kosasih; Farida Yuliaty; Rahadian Malik; Fitriana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study was conducted due to increasingly fierce competition in the healthcare industry and patients' low tendency to recommend, reuse, and make Clinic A in Kudus City their first choice. The aim was to obtain empirical evidence regarding the influence of brand image and service quality on patient loyalty through patient satisfaction as an intervening variable. The method used was descriptive verification analysis with a quantitative approach. Data were collected through questionnaires distributed to patients at Clinic A in Kudus City. The sample size was determined using Hair's formula, which is five to ten times the number of research indicators. Data analysis was performed using path analysis and the Sobel test to examine the mediating role. The results the analysis show that brand image, service quality, patient satisfaction, and patient loyalty are good. Partially and simultaneously, brand image and service quality have a positive and significant effect on patient satisfaction and loyalty. Patient satisfaction is also proven to mediate the effect of brand image and service quality on patient loyalty. Therefore, Clinic A in Kudus City is advised to continue to improve its brand image and service quality in order to strengthen patient satisfaction and loyalty on an ongoing basis.